School Factors as Moderators of the Relationship Between Physical Child Abuse and Pathways of Antisocial Behavior - Klika, J. Bart (2012)
Physical child abuse is a predictor of antisocial behavior in adolescence and adulthood. Few studies have investigated factors that moderate the risk of physical child abuse for later occurring outcomes, including antisocial behavior. The current analysis uses data from the Lehigh Longitudinal Study to investigate the prediction of antisocial behavior from physical child abuse and the buffering role of 3 school-related factors (i.e., school commitment, school dropout, and IQ) which are hypothesized to change the course of antisocial behavior from childhood into the adult years. Results show an association between physical child abuse and early antisocial behavior. Early antisocial behavior predicts antisocial behavior in adolescence, and that, in turn, predicts antisocial behavior in adulthood. Child IQ moderated the relationship between child physical abuse and antisocial behavior in childhood. However, no other moderation effects were observed. Limitations and implications for future research and prevention are discussed.